Intraneuronal accumulation of amyloid-β peptides as the pathomechanism linking autism and its co-morbidities: epilepsy and self-injurious behavior — the hypothesis - Frackowiak, Janusz; Mazur-Kolecka, Bozena (Frontiers in Molecular Neuroscience, 2023)
Autism spectrum disorder (ASD) is associated with enhanced processing of amyloid- precursor protein (APP) by secretase-α, higher blood levels of sAPPα and intraneuronal accumulation of N-terminally truncated A peptides in the brain cortex — mainly in the GABAergic neurons expressing parvalbumin — and subcortical structures. Brain A accumulation has been also described in epilepsy—the frequent ASD co-morbidity. Furthermore, A peptides have been shown to induce electroconvulsive episodes. Enhanced production and altered processing of APP, as well as accumulation of A in the brain are also frequent consequences of traumatic brain injuries which result from self-injurious behaviors, another ASD co-morbidity. We discuss distinct consequences of accumulation of A in the neurons and synapses depending on the A species, their posttranslational modifications, concentration, level of aggregation and oligomerization, as well as brain structures, cell types and subcellular structures where it occurs. The biological effects of A species which are discussed in the context of the pathomechanisms of ASD, epilepsy, and self-injurious behavior include modulation of transcription—both activation and repression; induction of oxidative stress; activation and alteration of membrane receptors’ signaling; formation of calcium channels causing hyper-activation of neurons; reduction of GABAergic signaling — all of which lead to disruption of functions of synapses and neuronal networks. We conclude that ASD, epilepsy and self-injurious behaviors all contribute to the enhanced production and accumulation of A peptides which in turn cause and enhance dysfunctions of the neuronal networks that manifest as autism clinical symptoms, epilepsy, and self-injurious behaviors.